2022
DOI: 10.1038/s41588-022-01095-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing diversity in genomics requires investment in equitable partnerships and capacity building

Alicia R. Martin,
Rocky E. Stroud,
Tamrat Abebe
et al.

Abstract: Calls for diversity in genomics have motivated new global research collaborations across institutions with highly imbalanced resources. We describe practical lessons we have learned so far from designing multidisciplinary international research and capacity-building programs that prioritize equity in two intertwined programs — the NeuroGAP-Psychosis research study and GINGER training program — spanning institutions in Ethiopia, Kenya, South Africa, Uganda and the united States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Along with previous studies, our results emphasize the importance of powerful PGS training in non-European cohorts 32 to improve the PGS performance for individuals from diverse genetic background. To narrow the prediction gap and ameliorate consequent health disparities between European and non-European ancestries individuals, concerted global effort and equitable collaborations are needed to increase the sample size of underrepresented individuals 32,33 . Equally important is the development of multi-ancestry PGS methods that can effectively leverage ancestrally diverse populations to train PGS models 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with previous studies, our results emphasize the importance of powerful PGS training in non-European cohorts 32 to improve the PGS performance for individuals from diverse genetic background. To narrow the prediction gap and ameliorate consequent health disparities between European and non-European ancestries individuals, concerted global effort and equitable collaborations are needed to increase the sample size of underrepresented individuals 32,33 . Equally important is the development of multi-ancestry PGS methods that can effectively leverage ancestrally diverse populations to train PGS models 34 .…”
Section: Discussionmentioning
confidence: 99%
“…As many have written before 15 , ensuring that scientific teams include and are led by people from groups harmed by weaponized science is one step that will make science more robust to misinterpretation and appropriation.…”
Section: Steps To Robustnessmentioning
confidence: 99%
“…It has been reported that over 80% of genomics data sets are made up of individuals from European ancestry. 20 This poses a serious data diversity and representation issue in precision medicine. 21 Studies have shown that mitigation methods for racial bias in data can increase fairness, avoid inequities in diagnosis and medical care.…”
Section: Discussionmentioning
confidence: 99%